Effectiveness of Diacerein in Primary Knee Osteoarthritis - Muhammad Ammar Naqvi, Omer Iqbal Cheema, Usman Latif, M. Saif-ur-Rehman, Jahan Zeb Khan, Zahid Shafiq, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine role of diacerein among the patient with primary knee osteoarthritis (KOA). Study Design: An observational cohort study. Place and Duration: Department of orthopedic surgery, Sughra Shafi Medical Complex, Narowal from June 2021 to May 2022. Materials and Methods: A total of 100 patients of either gender visiting outpatient department with primary KOA aged 50-75 years were enrolled. Patients were assessed as per Western Ontario and McMaster Universities Arthritis Index (WOMAC) and visual analogue scale (VAS). Diacerein was prescribed 100 mg two times a day for a total duration of six months. WOMAC and VAS were noted before and after completion of the 6 months follow up period. Results: In a total of 100 patients, 56 (56.0%) were female. Mean age was 63.58 ± 6.42 years while mean BMI was 29.46±3.42 kg/m2. There were 50 (50.0%) patients who belonged to middle socioeconomic status. Grade of KOA was II in 54 (54.0%) patients. Baseline WOMAC score was 45.12±6.68 while baseline VAS was noted to be 6.81±2.76. At the end of the 6-month treatment period, 83 patients completed the treatment span and so were included in the final analysis. It was found that significant reduction in both WOMAC score (p<0.0001) and VAS (p<0.0001) were found among the studied patients. Practical Implications: Diacerein seems to be a good option for relief in symptoms against patients suffering with primary knee osteoarthritis but further randomized trials should be conducted to verify the findings of this study. Conclusion: Diacerein resulted in significant improvement in the mean WOMAC and VAS scores after six months therapy. Keywords: Diacerein, improvement, Osteoarthritis Knee, VAS, WOMAC